Pathomorphologic investigations on the genital system of ewes II. Uterus, cervix and vagina - Karadas, E; Timurkaan, N (Scientific Technical Research Council Turkey, 2001)
This study was carried out to determine the pathomorphologic changes and the incidence of these changes in the uterus, cervix, vagina and related ligaments of ewes slaughtered at Elazig abattoirs. For this purpose, the genital organs of 6100 ewes from different breeds and ages were examined, There were pathomorphologic changes in 274 cases (4.49 %) in the uterus. 70 cases (1.14 %) in the cervix, and 61 cases (1.00 %) in the vagina. Inflammatory changes were primarily lesions (2.68 %) observed in the uterus. These changes were catarrhal endometritis (0.52 %). purulent metritis (0.32 %), necrotic endometritis (0.11 %), chronic nonpurulent endometritis (0.95 %), granulomatous endometritis (0.13 %), pyometra (0.11 %) and parametritis (0.52 %). In addition, endometrial hyperplasia (0.36 %), hydrometra (0.34 %). uterus unicornis (0.16 %). infantilism (0.14 %) and melanosis (0.85 %) were also seen in the uterus. Inflammatory conditions were observed in 0.68 % of cases in the cervix, and it was noted that 69.04 % of cervicitis was accompanied by inflammations of the uterus. Furthermore, infantilism (0.14 %), metaplasia (0.26 %), melanosis (0.08 %) and abscesses on the serosa (0.13 %) were also found in the cervix. Vaginitis (0.55 %), severe hyperplastic changes (0.19 %) in the mucosa, Gartner's ducts cyst (0.01 %) in the submucosa, abscesses on the serosa (0.08 %), and infantilism (0.14 %) were the major pathomorphologic findings observed in the vagina.
Keywords: ewe; uterus; cervix; vagina; pathomorphology